A paideia grega: a formação omnilateral em Platão e Aristóteles - Oliveira, José Sílvio de (2015)
The objective of this thesis is to investigate the meaning and the genesis of Greek paideia in, having as parameters Plato‟s (427 a. C.) and Aristotle‟s (348 a. C.), educational concepts. We understand that the educational philosophies in this sense these classical thinkers of ancient Greece is also essential to understand the nature and the meaning of education , as well as reflect on the possibility and necessity of its political value , as formulated by these two philosophers. The problem to be solved can be expressed by the question: to what extent the Greek education founded in the philosophies of Plato and Aristotle can provide valid and universal principles, when we think about a fair, equitable State where the principle of civility can educate the omnilateralmente man? The thesis focuses specifically on the masterpieces of the two thinkers Plato: The Republic, Laws and The Political; Aristotle: Politics, Ethics Nicômacos and Metaphysics and The principal authors who interpret, feature, underpin and guide the research path in Plato and Aristóteles are: Mario Alighiero Manacorda; Werner Jaeger; Moses I. Finley; Jean-Pierre Vernant and Herni - Irenee Marrou, Herodotus, Hesiod, Homer, Cesar Aparecido Nunes, Ildeu Moreira Coêlho, Maria do Céu Fialho, José Ribeiro Ferreira e Delfim Ferreira Leão. Complementary Bibliography both Brazilians as foreign authors was consulted. Our research, therefore, by its own nature, is based on studies of bibliographic order and attempts to answer the question about the value of Plato‟s and Aristotle‟s principles for understanding education as full human development.